Answer:
y - 4 = 2/3 (x + 1)
Step-by-step explanation:
The point-slope equation has the following form:
![y-y_0=m(x-x_0)](https://img.qammunity.org/2023/formulas/mathematics/college/ehyjo1n0rdvlf4cxbixkhiqlxiykoxywnz.png)
Where (x0, y0) is a point and m is the slope of the line.
The slope can be calculated as:
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/78uaqhwt0aws3qfwxigaftpihnmb1gzxtp.png)
Where (x1, y1) and (x2,y2) are two points in the line.
So, replacing (x1, y1) by (-1, 4) and (x2, y2) by (-4, 2), we get:
![m=(2-4)/(-4-(-1))=(-2)/(-4+1)=(-2)/(-3)=(2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/eo1g05hukhrgg7j73shpush9dqlb9bzj8o.png)
Then, replacing m by 2/3 and (x0, y0) by (-1, 4), we get that the equation of the line is:
![\begin{gathered} y-4=(2)/(3)(x-(-1)) \\ y-4=(2)/(3)(x+1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6xhg8yop84b6p50d631l0ehjueo0abj6ry.png)
So, the answer is:
y - 4 = 2/3 (x + 1)